Endoscopic suturing as a less invasive approach for the treatment of anastomotic leakage after esophagogastrostomy – a case report - Schlosser, Tobias; Feisthammel, Juergen; Gockel, Ines; Mössner, Joachim; Hoffmeister, Albrecht (Zeitschrift für Gastroenterologie, 2018)
Anastomotic leakage is a frequent complication after gastrointestinal (GI) surgery and is associated with high morbidity and mortality. Endoluminal therapy offers numerous advantages compared to surgical revision. We present the case of a 74-year-old female patient with anastomotic leakage after esophagogastrostomy. The defect was closed using the OverStitch endoscopic suturing system with immediate technical and clinical success. Hereby, an example of the feasibility of this novel technique in a case of anastomotic leakage is presented and provides an outlook for the rising importance of endoscopic therapy.
Keywords: anastomotic leakage; endoscopic suturing; surgical endoscopy; full thickness repair of gastrointestinal defect